Business Strategy Approach to Informal Small Businesses in Increasing Productivity and Competitiveness - Muhammad Mansur; Abdul Kodir Djaelani (Manunggal Halim Jaya, 2023)
The aim of this study is to analyze (1) performance on production capabilities, (2) Market orientation on performance, (3) innovative performance, (4) Performance on work productivity, (5) Production capacity on competitiveness, (6) Market orientation on competitiveness (7) Innovative on competitiveness (8) Work productivity on competitiveness (9) Performance on competitiveness. The research used primary data by surveying as many as 187 Informal small business respondents in Surabaya city as samples. Research data were analyzed using Structural Equation Modeling (SEM). The results of this study states: (1) Production capacity significantly on performance, (2) Market orientation was not significantly on performance, (3) Innovative have significant effect on performance, (4) work productivity have a significant effect on performance (5) production capacity of influential have significant effect on competitiveness, (6) Market orientation have a significant effect on competitiveness, (7) Innovative have a significant effect on competitiveness (8) Work productivity have significant effect on competitiveness (9) Performance have a significant effect on competitiveness (10) Production capabilities have a significant effect on competitiveness through Performance, (11) Market orientation do not have effect on competitiveness through performance, (12) Innovative have a significant effect on competitiveness through performance, (13) Work productivity have a significant effect on competitiveness through performance.